Factors associated with changes in community ability and recovery after psychiatric rehabilitation : a retrospective study - Tan, Bhing-Leet (2019)
One of the key goals of psychiatric rehabilitation is to return individuals with mental illnesses back into the community via restoration of the necessary skills. This retrospective study seeks to evaluate the factors associated with improvement in community functioning after a period of outpatient rehabilitation. 223 individuals enrolled into three broad rehabilitation groups—clinical, vocational and creative therapies/individual sessions—were included in this study. The Multnomah Community Ability Scale (MCAS) and Milestones of Recovery Scale (MORS) were used to evaluate each individual before and after the rehabilitation programme. Across all three groups, there were significant improvements in MCAS scores and MORS ratings. In multivariate models, clinical rehabilitation group was superior to creative therapies/individual sessions in predicting MORS change. The study also revealed a close relationship between recovery gains and improvement in community ability.